Flare-out conditions in static thin-shell wormholes - Mazharimousavi, S. Habib; Halilsoy, Mustafa (Physical Review D, American Physical Society (APS), 2014)
We reconsider the generalized flare-out conditions in static wormhole throats given by Hochberg and Visser. We show that due to the presence of matter sources on the throat, these conditions are not applicable to the thin-shell wormholes.
The file in this item is the publisher version (published version) of the article.
Keywords: general relativity; black holes